Assessment of the Possibility of Using Reclaimed Materials for Making Cores by the Blowing Method - Dańko, R.; Dańko, J.; Skrzyński, M. (Archives of Foundry Engineering, 2017)
The cumulative results of investigations of the possibility of using the reclaimed materials after the mechanical, thermal or mechanical-thermal reclamation for making cores by means of the blowing method in the alkaline CO2 technology, are presented in the paper. Three kinds of spent sands: with furfuryl resin, bentonite and alkaline phenolic resin, obtained from the foundry, were subjected to three kinds of reclamation: mechanical, thermal and combined mechanical-thermal, applying for this aim adequate experimental devices. The obtained reclaims were assessed with regard to the degree of the matrix liberation from the determined binding material. Reclaims of moulding sands with binders of the form of resin were assessed with regard to ignition loss values and pH reaction, while reclaims of moulding sands with bentonite with regard to the residual clay content and pH value. In all cases the results of the performed sieve analyses were estimated and the average characteristic diameter dl was determined. The reclaimed matrix was applied as a full substitute of the fresh high-silica sand in typical procedures of preparing core sands used for making shaped samples for bending strength investigations, Rg u .
Keywords: Moulding sand; reclamation; Environmental protection